Influence of feeding different types feed blocks as supplementary feed on the reproductive performance of Awassi ewes grazing cereal stubble: A. D. Salman , Hadeel K. Ibrahim , D. A. Ali , R. A. Ibrahim - Salman, A. D. (The Iraqi Journal of Veterinary Medicine, 2005)
This study was conducted to investigate the Influence of feeding different types feed blocks as supplementary feed on the reproductive performance of Awassi ewes grazing cereal stubble. These types were feed blocks enriched with cottonseed meal (CSM) or Brewers’ grain (BG) as sources undegradable protein (UDP). Ninety-six Awassi ewes (mean live weight 42.2 Kg), aged 3-4 years were allocated into three groups according to ewes live weight and body condition score.Group (C): Control (No Supplement) stubble grazing only.Group (FBC): FB enriched with CSM supplement plus stubble grazing.Group (FBB): FB enriched with BG supplement plus stubble grazing.All ewes were run as one flock during cereal stubble grazing. The feed blocks were fed to animals (supplementary groups) after their return from grazing wheat and barley stubble (28 days prior to mating and 54 days after introduction of rams). Rams run with the flock during the mating period. The results showed that feeding feed blocks enriched with CSM and BG as supplementary feed resulted considerable improvement in weight gain (P<0.05), body condition score (P<0.05), conception rate (13-16), lambing percentage (25-33%), twinning percentage (13-18%) and decreased the proportion of barren ewes (19 vs. 6 and 3%). Inclusion of small amount of high moisture brewers grain by-product (9%) as sources of undegradable protein in the feed blocks formula as replacement for costly cottonseed meal resulted a dramatic effects on the reproductive performance of Awassi ewes especially twinning rates and lambing rate.